2016
DOI: 10.1136/gutjnl-2015-310096
|View full text |Cite
|
Sign up to set email alerts
|

Raf kinase inhibitor protein mediates intestinal epithelial cell apoptosis and promotes IBDs in humans and mice

Abstract: RKIP contributes to colitis development by promoting inflammation and mediating IEC apoptosis and might represent a therapeutic target of IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 43 publications
2
53
0
Order By: Relevance
“…These results are concordant with a recent study that suggested positive correlation between RKIP (a kinase upstream to TAK1) activation and disease severity in IBD patients, as well as between RKIP and TAK1 phosphorylation in DSS and TNBS models of colitis (Lin et al. ). Our immunofluorescence studies indicated elevated p‐TAK1 expression, prominently in nonepithelial cells (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are concordant with a recent study that suggested positive correlation between RKIP (a kinase upstream to TAK1) activation and disease severity in IBD patients, as well as between RKIP and TAK1 phosphorylation in DSS and TNBS models of colitis (Lin et al. ). Our immunofluorescence studies indicated elevated p‐TAK1 expression, prominently in nonepithelial cells (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Raf kinase inhibitor protein (RKIP) promoted intestinal epithelial cell apoptosis in human and mouse IBD via interaction with TAK1 (Lin et al. ). Also, a recent GWAS study suggested association of TAB 2, a TAK1‐binding protein with IBD (Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…We next asked whether CD177 + neutrophils could maintain intestinal barrier integrity. WT and CD177 −/− mice were fed with fluorescein isothiocyanate (FITC)-dextran (500 mg/kg) 4 hours before anesthetisation on day 10 as described previously,39 40 and the levels of FITC-dextran in sera were detected by ELISA. As shown in figure 6G, CD177 −/− mice displayed significantly higher serum levels of FITC-dextran compared with WT mice after DSS exposure.…”
Section: Resultsmentioning
confidence: 99%
“…This response is characterized by the recruitment of immune cells and the production of proinflammatory cytokines via the activation of transcription factors, such as NF-κB (5,6). These cytokines typically clear invading bacteria and protect the body from infection; however, under pathogenic conditions, they induce IEC death and further impair epithelial integrity, thereby creating a vicious cycle and eventually leading to IBD (3,(7)(8)(9). Among the cytokines implicated in colitis, TNFα is the best studied, and its overproduction is a hallmark of IBD.…”
mentioning
confidence: 99%